Suppressing Bacterial Wilt (Ralstonia solanacearum) by Grafting Tomato Seedlings Grown on Six Comparable Media - Anggita Rahmawati; Triwidodo Arwiyanto (Universitas Gadjah Mada, 2020)
Bacterial wilt caused by Ralstonia solanacearum is an important disease of tomatoes. The grafting method with a resistant rootstock variety is a reliable control technique and has been carried out in many countries. Healthy tomato seedling are needed for grafting so this study was aimed to find a good seedling medium to grow the upper stem and rootstock of tomato for grafting and to know the effect of seed media on the intensity of bacterial wilt). Tomato seeds were grown in coir and rice husk charcoal with ratio A (10:0), B (9:1), C (8:2), D (7:3), E (6:4), F (5:5) (coir : rice husk charcoal, v/v). Seedlings were watered regularly and after seedlings aged 21 days, the grafting was conducted. Agronomic observations were justified by measuring germination style, plant height, leaf area, fresh mass and dry mass of plants at 21 days after planting. Tomato seedlings were grafted by using H-7996 variety as a rootstock and Servo variety as an upper stem. Tomato seedlings were transplanted into polybags and then inoculated with R. solanacearum (108 CFU/ml). The disease intensity and AUDPC (Area Under Disease Progress Curve) were recorded. The results revealed that the media with a ratio of 8:2 (coir : rice husk charcoal, v/v) is the best medium for growing tomatoes and the grafting treatment could reduce the disease intensity of bacterial wilt by 40% compared with non grafted treatment and reduce 16% disease intensity compared to the grafted treatment with seedling sown in other ratio media at the last observation.